Cold shock Y-box binding protein-1 acetylation status in monocytes is associated with systemic inflammation and vascular damage. (November 2018) - Ewert, Lara; Fischer, Anja; Brandt, Sabine; Scurt, Florian G.; Philipsen, Lars; Müller, Andreas J.; Girndt, Matthias; Zenclussen, Ana C.; Lindquist, Jonathan A.; Gorny, Xenia; Mertens, Peter R.
Abstract: Background and aims: In dialysis patients, vascular morbidities are highly prevalent and linked to leukocyte extravasation, especially of polarized monocytes. Experimental data demonstrate that phenotypic changes in monocytes require Y-box binding protein-1 (YB-1) upregulation. Methods: We determined YB-1 expression in circulating and vessel-invading monocytes from healthy controls and dialysis patients to correlate results with intima plaque formation and systemic inflammation. Results: Compared to healthy subjects, dialysis patients have fewer classical and more intermediate and non-classical monocytes. Post-translationally modified YB-1 (lysine 301/304 acetylation) is detected at high levels in the nucleus of adherent and invading CD14 + CD68 + monocytes from umbilical cord and atherosclerosis-prone vessels. The content of non-acetylated YB-1 is significantly decreased ( p  < 0.001), whereas acetylated YB-1 is correspondingly increased ( p  < 0.001) throughout all monocyte subpopulations, such that the overall content remains unchanged. Conclusions: In dialysis patients the YB-1 acetylation status is higher with prevailing diabetes and intima plaque formation. Pro-inflammatory mediators TNFα, IL-6, uPAR, CCL2, M-CSF, progranulin, ANP, and midkine, as well as anti-inflammatory IL-10 are significantly increased in dialysis patients, emphasizing a systemic inflammatory milieu. Strong positive correlations of monocytic YB-1 content are seen with ANP, IP-10, IL-6, and IL-10 serum levels. This is the first study demonstrating an association of cold shock protein YB-1 expression with inflammation in hemodialysis patients. Highlights: In hemodialysis (HD) patients the level of acetylated YB-1 is increased (p < 0.001) in all monocytic subpopulations. In HD patients with vascular damage (intima plaques, increased intima media thickness) alterations of monocytic YB-1 content are apparent. Serum cytokine levels show a close correlation between monocytic YB-1 content and systemic inflammatory status. The correlation of monocytic YB-1 content with disease and systemic inflammation suggests a causal link.